Expression of acidic fibroblast growth factor (aFGF) and fibroblast growth factor receptor 4 (FGFR4) in breast fibroadenomas. Issue 1 (1st January 2001) - Rosa, S La; Sessa, F; Colombo, L; Tibiletti, M G; Furlan, D; Capella, C
Abstract : Background/Aim —Fibroadenomas are benign tumours composed of both glandular and fibrous tissue. The mechanisms regulating the growth of these tumours and the relation between the stromal and epithelial cells are poorly understood. Acidic fibroblast growth factor (aFGF) is a well known fibroblast activator, which acts through four specific cell surface receptors, among which, fibroblast growth factor receptor 4 (FGFR4) is highly specific. The aim of this study was to evaluate the distribution of aFGF and FGFR4 in specific cell types of fibroadenomas to understand their possible role in the growth of these breast lesions. Methods —Formalin fixed and paraffin wax embedded tissues from 15 fibroadenomas and peritumoral normal breasts were investigated for the expression of aFGF and FGFR4 using immunohistochemistry. The presence of aFGF mRNA was also investigated using in situ hybridisation. Results — Immunoreactivity for aFGF and FGFR4 was seen in epithelial cells, but it was lacking in myoepithelial cells of both normal tissues and fibroadenomas. Strong FGFR4 immunoreactivity was found in stromal fibroblasts, which were also weakly positive for aFGF. aFGF mRNA was detected in epithelial cells and in some stromal fibroblasts. Conclusions —These results suggest a paracrine/autocrine modulation of epithelial and stromal cells of fibroadenomas through an aFGF–FGFR4 interaction. This interaction might regulate various cell functions and the growth of fibroadenomas.